The Astonishing Power of Storytelling Leading, Teaching, and Transforming in a New Way. - Garmston, Robert John (SAGE Publications, 2018)
Master the secret to engaging any audience, from classrooms to colleagues. Everyone loves a good story. More than entertainment, stories told well captivate listeners and motivate action. This guidebook shows how to leverage the power of storytelling to engage and persuade any audience. Featuring current cognitive neuroscience research and updated references, the book includes: Detailed breakdowns of the essential elements all great stories share, and templates for creating yours Tips for supercharging your stories by drawing from personal experience as well as familiar movies, TV shows, a.